An Analysis Of The Suitability Of Adapting Istana Jahar To Be A Royal Museum Using Green Building Index Tools - Siti Aisyah Muhammad , Nur Athmar Hashim; Tengku Fauzan Tengku Anuar (International Journal of Advanced Science and Technology, 2020)
The conversion of Istana Jahar, a traditional Malay building, gives rise to a conflict between preserving the heritage building or renovating excessively to create a proper museum in which to place valuable artifacts. This article analyses the appropriateness of adapting Istana Jahar, Kelantan, by converting it into a royal museum using recommended Green Building Index tools. Istana Jahar was a presidential palace built using traditional Malay architectural technology with two-story timber construction. It is the only building in Kelantan that has been listed on the National Heritage Register List and has the highest national heritage recognition. At present, no vernacular building based on traditional Malays architecture has been certified as a green building. This study assessed the suitability of adapting a reused building into a sustainable heritage building. Four main components were examined; ventilation, wind flow, lighting, and solar study. The ventilation system was assessed using a survey administered to 95 participants on air quality comfort in the building. Computational Fluid Dynamics (CDF) was used to assess wind flow across the building and determine the suitability of applying natural ventilation. Lighting was examined using a survey administered to the same participants regarding the satisfaction of the lumen towards the artifacts displayed and the spaces inside the building. Simulation of a solar path record at the building using Autodesk Revit determined natural lighting and internal temperature. The findings showed that Istana Jahar had not been adequately designated as a museum as artifacts are exposed directly to high temperature inside the building. As a museum, daytime temperature and sunlight need to be considered in Istana Jahar, whereby the interior must be fitted with an air-conditioning system to preserve the artifacts displayed. Thus, Istana Jahar is most appropriate for preservation as a heritage building and is not suitable to adopt as a royal museum without excessive renovation.